The Second Canadian Symposium on Hepatitis C Virus: A Call to Action. (2013) - Grebely, Jason; Bilodeau, Marc; Feld, Jordan J; Bruneau, Julie; Fischer, Benedikt; Raven, Jennifer F; Roberts, Eve; Choucha, Norma; Myers, Rob P; Sagan, Selena M; Wilson, Joyce A; Bialystok, Frank; et al.
Abstract : In Canada, hepatitis C virus (HCV) infection results in considerable morbidity, mortality and health-related costs. Within the next three to 10 years, it is expected that tolerable, short-duration (12 to 24 weeks) therapies capable of curing >90% of those who undergo treatment will be approved. Given that most of those already infected are aging and at risk for progressive liver disease, building research-based interdisciplinary prevention, care and treatment capacity is an urgent priority. In an effort to increase the dissemination of knowledge in Canada in this rapidly advancing field, the National CIHR Research Training Program in Hepatitis C (NCRTP-HepC) established an annual interdisciplinary Canadian Symposium on Hepatitis C Virus. The first symposium was held in Montreal, Quebec, in 2012, and the second symposium was held in Victoria, British Columbia, in 2013. The current article presents highlights from the 2013 meeting. It summarizes recent advances in HCV research in Canada and internationally, and presents the consensus of the meeting participants that Canada would benefit from having its own national HCV strategy to identify critical gaps in policies and programs to more effectively address the challenges of expanding HCV screening and treatment.